« Chez nous, on ne tue pas le chien sans raison » - Christian Seignobos (Revue d'ethnoécologie)
For the societies of the northern Mandara Mountains (North Cameroon), the dog has kept a part of humanity up to sharing with the family the sacrifices to the ancestors’ manes and standing like a kind of guardian of the family morality.“Myths” set out to recall the eminent services dog rendered to mankind. The patterns of matrimonial alliances have widely addressed this in the past.To kill a dog with iron is a crime, to let it starve to death, a heavy infamy. Yet humans had, not long ago, to sacrifice dogs during peace oaths and, still today, to satisfy a cynophagy which relates more to therapeutic care than to diet.